Dust emission in northern China: atmospheric emission–dispersion modelling of a major dust event. Issue 12 (27th January 2013) - Pasqui, Massimiliano; Taramelli, Andrea; Barbour, Jonathan; Kirschbaum, Dalia; Bottai, Lorenzo; Busillo, Caterina; Calastrini, Francesca; Gualtieri, Giovanni; Guarnieri, Francesca; Small, Chris
ABSTRACT: Comprehensive modelling of dust events requires a full physical representation of small‐scale emission mechanisms and description of long‐range transport dynamic. In this paper we propose a simulation system that integrates three different models in order to represent the whole dust cycle. The RAMS atmospheric model configuration has two nested grids, at 50 km and 10 km horizontal resolution, and is used to force both the dust emission model DUSTEM, and the transport model CAMx. The performance of the three‐model simulation system was evaluated using a major dust storm that occurred in March 2002 in the desert of the Alashan Prefecture (Inner Mongolia, China) and which had a significant impact over a large area in northern China. In order to identify potential active dust sources, a specific remote sensed analysis, calibrated through a field campaign in the Alashan Prefecture region, has been assimilated in the modelling system. Simulated dust storm features, from the higher resolution grid, are in good agreement with observed data: surface wind values discrepancies are less than 2 m/s in the Alashan area and less than 5 m/s along the dust storm track. In comparison to ground observations, the modelled dust surface concentration peaks in Beijing differ by only 2 mg/m 3 although the timing of dust peaks is delayed in the model. As a consequence this integrated numerical model, along with the remote sensed land surface characterization, is suggested to be a practical and flexible tool for simulating and analysing the whole dust storm dynamics. Copyright © 2013 John Wiley & Sons, Ltd.